Integrated modelling of production, marketing and financial functions of a company based on a corporate planning approach: case study of the Algerian national marble company - NIBOUCHE, Fatima; BELMOKHTAR, Oum-hani (Cuadernos de Estudios Empresariales, 2010)
In today’s dynamic and competitive environment, planning for effective use of the company resources requires an analytical and integrated approach of its essential functions. With such goal in mind, the corporate planning model, in which the modules of production and marketing are related to the financial module, presents a very efficient solution. It is particularly well suited for the needs of Algerian companies operating in an environment that has undergone a transformation from planned economy to market economy where risks and uncertainties are ubiquitous. Furthermore, Algerian companies should take account of the importance of strategic planning and forecasting where, in that context, the corporate planning model provides a powerful tool for decision-making. This work provides a corporate planning model specified for the Algerian National Marble Company. The presented model has been devised and validated from the company data to generate physical and financial short-term forecasts. The obtained empirical results show the usefulness of such a model for the managers in terms of providing a precise model of the essential functions of the company, helping to evaluate the consequences of different management scenarios and assisting in the decision-making process. Furthermore, using prospectivesimulations, the presented model can be used as a tool for forecasting.